2020
DOI: 10.4102/phcfm.v12i1.2387
|View full text |Cite
|
Sign up to set email alerts
|

Mixed-methods evaluation of family medicine research training and peer mentorship in Lesotho

Abstract: Background: Strengthening primary care research capacity is a priority globally. Family medicine training programmes in sub-Saharan Africa represent an important opportunity to build primary care research; however, they are often limited by insufficient research training and mentorship. Peers can be used to extend research mentorship capacity, but have not been evaluated in this context.Aim: The aim of this study was to evaluate one family medicine training programme’s research capacity building efforts throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 27 publications
1
23
0
Order By: Relevance
“…A total of 14 strategies and 11 studies 27,31,[34][35][36][37][38][39][40][41][42] demonstrated that digital tools enhanced research mentorship in LMICs. Digital tools including apps, websites, and other web-based platforms to aid in mentor/mentee matching, communication, establish and sustain mentorship relationship over time (14 submissions).…”
Section: Digital Tools To Support Mentorshipmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 14 strategies and 11 studies 27,31,[34][35][36][37][38][39][40][41][42] demonstrated that digital tools enhanced research mentorship in LMICs. Digital tools including apps, websites, and other web-based platforms to aid in mentor/mentee matching, communication, establish and sustain mentorship relationship over time (14 submissions).…”
Section: Digital Tools To Support Mentorshipmentioning
confidence: 99%
“…Fifteen open call strategies and 49 studies 19,20,[22][23][24][25][26][27][28][29][30][31][32]35,37,38,40,42, showed that leveraging existing research and training programs facilitated research mentorship. Already existing training programs with databases of staff, contacts/institutions that can be partnered with to network on mentorship and leverage other institution's resources is beneficial for facilitating sustainability research mentorship.…”
Section: Leveraging Existing Research and Training Resourcesmentioning
confidence: 99%
See 3 more Smart Citations